History and organizational legitimacy: reflections on the organizational-historical narratives - Santos, Larissa Conceição dos (Organicom, 2014)
History is also (re)constructed currently through the rememorations, narrations, and mnemonic reenactments. In this article we analyze the place of history in organizations and its interface with organizational communication, highlighting the role of narratives for their legitimation. The construction of the organizational-historical narratives is observed as a strategy that legitimately seeks to provide coherence to the organizational activity and highlight its social function.